Repetitive Transcranial Magnetic Stimulation on the Affected Hemisphere Enhances Hand Functional Recovery in Subacute Adult Stroke Patients: A Randomized Trial - Yang, Yawen; Pan, Huijuan; Pan, Wenxiu; Liu, Yang; Song, Xiaohui; Niu, Chuanxin M.; Feng, Wuwei; Wang, Jixian; Xie, Qing (Frontiers in Aging Neuroscience, 2021)
Objectives: Either motor training or repetitive transcranial magnetic stimulation (rTMS) could modulate the neural plasticity after stroke. Therefore, synchronizing the two interventions may optimize the efficiency of recovery. In the present study, we aim to investigate the effect of rTMS along with hand grip training on the neurobehavioral and hand functional recovery in one cohort of subacute stroke patients. Methods: Thirty-nine stroke patients were enrolled in a single-center, single-blinded, randomized clinical trial. We tested different intervention effects of rTMS and hand grip training (group A), rTMS alone (group B), and hand grip training alone (group C). For the rTMS-treated groups, patients received 10 consecutive sessions of 5-Hz stimulation over the affected hemisphere with 750 pulses. Jebsen–Taylor Hand Function Test (JTHFT), Fugl-Meyer assessment of upper extremity (FMA-UE), grip strength, modified Barthel index (mBI), and ipsilesional motor evoked potential (iMEP) latency were assessed and compared across the groups. Results: We found that only rTMS along with hand grip training group all improved in JTHFT, FMA-UE, grip strength, and mBI (p ≤ 0.01) compared with the baseline among the three groups. Furthermore, this study demonstrated that rTMS plus hand grip training had much better results in improvement of neurobehavioral outcomes compared to the rTMS alone- and hand grip training alone-treated patients (p < 0.05). However, no significant differences were detected in neurophysiologic outcome between intra-groups and inter-groups (p > 0.05). Conclusion: These proof-of-concept results suggested that rTMS alone with hand grip training was a unique approach to promote hand functional recovery in stroke patients. It provided important information to design a large-scale multi-center clinical trial to further demonstrate the efficiency of the combination of central and peripheral stimulation. Clinical Trial Registration:http://www.chictr.org.cn (#ChiCTR1900023443).